The Education of Multiple Family Members and the Life-Course Pathways to Cognitive Impairment. (26th March 2020) - Yahirun, Jenjira J; Vasireddy, Sindhu; Hayward, Mark D
Abstract: Objectives: This article asks how the educational attainments of multiple family members, including parents and offspring, are associated with the cognitive health of older adults in the United States. Methods: We use panel data from the U.S. Health and Retirement Study (2000–2012) to examine how the education of an individual, their parent(s), and their offspring are associated with the prevalence of moderate/severe cognitive impairment and the onset of cognitive impairment among older adults using logistic regression and discrete-time event history analysis, respectively. Results: We found that when combined, only the education of the individual is inversely associated with cognitive impairment at baseline. However, both the educational attainments of an individual and their offspring are negatively associated with the risk of becoming cognitively impaired, among individuals who were not already cognitively impaired. Conversely, parental education was not predictive of being cognitively impaired or the onset of impairment. Furthermore, we found that respondent gender did not moderate the relationship between a family member's education and respondent cognitive health. Discussion: This study adds to current research by asking how resources from earlier and subsequent generations matter for older adults' cognitive health. Although we found little evidence that parental education matters at this life stage, results suggest that offspring education has a salient positive effect on later-life cognitive health. This finding underscores an overlooked source of health disparities—offspring resources—and highlights how a family perspective remains a powerful tool for understanding health inequalities in later life.